2015
DOI: 10.1038/ncomms9897
|View full text |Cite
|
Sign up to set email alerts
|

DNA repair factor BRCA1 depletion occurs in Alzheimer brains and impairs cognitive function in mice

Abstract: Maintaining DNA integrity is vital for all cells and organisms. Defective DNA repair may contribute to neurological disorders, including Alzheimer's disease (AD). We found reduced levels of BRCA1, but not of other DNA repair factors, in the brains of AD patients and human amyloid precursor protein (hAPP) transgenic mice. Amyloid-β oligomers reduced BRCA1 levels in primary neuronal cultures. In wild-type mice, knocking down neuronal BRCA1 in the dentate gyrus caused increased DNA double-strand breaks, neuronal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
181
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 166 publications
(194 citation statements)
references
References 70 publications
(132 reference statements)
11
181
1
1
Order By: Relevance
“…Supporting this notion are studies on the tumor suppressor BRCA1 that demonstrated that ablation of BRCA1 by Nestin-cre lead to severe brain growth defects [60]. Additionally, silencing of BRCA1 in the adult dentate gyrus leads to a similar behavioral phenotype as we observed in our adult-ablated CCNA2 mice [59]. These studies underscore the importance of the DNA damage response in embryonic neural progenitors as well as in adult neurons.…”
Section: Discussionsupporting
confidence: 80%
“…Supporting this notion are studies on the tumor suppressor BRCA1 that demonstrated that ablation of BRCA1 by Nestin-cre lead to severe brain growth defects [60]. Additionally, silencing of BRCA1 in the adult dentate gyrus leads to a similar behavioral phenotype as we observed in our adult-ablated CCNA2 mice [59]. These studies underscore the importance of the DNA damage response in embryonic neural progenitors as well as in adult neurons.…”
Section: Discussionsupporting
confidence: 80%
“…BRCA1 was also found to be reduced in the brains of AD patients and human amyloid precursor protein (hAPP) transgenic mice (Suberbielle et al, 2015). Since HR is not the pathway of choice in post-mitotic cells these results are difficult to interpret.…”
Section: Dsb Processing and Repair As A Function Of Agementioning
confidence: 99%
“…In the brains of AD patients, BRCA1 levels are reduced, and likewise DNA repair capacity is reduced. BRCA1 was also found reduced in AD mouse brains and BRCA1 depletion caused learning and memory deficits (Suberbielle et al, 2015). Thus, these results indicate that DNA damage normally occurs during brain activity and that if we can improve double strand break repair capacity in AD brains, aspects of AD may be ameliorated.…”
Section: Dna Damage In Admentioning
confidence: 99%